SPECIAL ASPECTS OF DESIGN-PROJECTING OF CHILDREN`S DRESSES FOR BALLROOM & SPORT DANCES - Рубанка, А. І.; Сінянська, Є. В.; Рубанка, М. М.; Остапенко, Н. В. (Art and Design, 2018)
Comprehensive study of the special aspects of design-projecting of children`s dresses for ballroom & sport dances; analysis of the assortment of the used materials; development of recommendations for the provision of ergonomic indicators of the design; development of the assortment range of dresses on the basis of systematization of the requirements for their design-projecting. Methods of comprehensive analysis of existing dresses for ballroom & sport dances are used in the work; analytical studies of the requirements for the selected assortment of clothing. In this workthe conditions of use of the clothes for ballroom & sport dances are analyzed; the choice of the materials for their manufacture is grounded. Special aspects of design-projecting of the dresses for girls, in particular their design and technological aspects, are studied. It is found that a number of specialized requirements are put forward to the selected assortment. On the basis of analytical studies, the assortment range of dresses for ballroom & sport dances for girls of junior school age has been developed. Reside in the development of the requirements for the girl`s clothes with the predicted ergonomic characteristics for ballroom & sport dances. It was formed and systematized an information base of the elements of the details and components of the dresses for ballroom & sport dances, it was proposed an assortment range of dresses for girls of junior school age